FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN ANEMIA PADA BADUTA USIA 6 - 23 BULAN DI WILAYAH UPTD PUSKESMAS DTP PEDES TAHUN 2023 - Lulu Mamluaturrohmah, (2023)
Background: Anemia is a condition where a child has insufficient hemoglobin (Hb) levels to provide adequate oxygen to body tissues. Anemia has been recognized as a worldwide health problem which is very vulnerable in children aged 6-24 months. The prevalence of anemia in the age range of 6-59 months based on WHO in 2019 in Indonesia is 38.4%. Objective: This study aims to determine the factors associated with anemia in baduta aged 6 - 23 months. Methods: This type of research is an observational analytic with a cross sectional design. By taking samples using the accidental sampling method and obtained 100 respondents who fit the inclusion and exclusion criteria. The research was conducted with questionnaire instruments, Food Frequency Questionare (FFQ), body length measurement, weight weighing and Hb examination using the Easytouch GcHb tool. Results: Factors associated with anemia in this study were child birth weight (p=0.004), history of infectious disease (p=0.003), mother's education (p=0.003), mother's age (p=0.042), maternal knowledge (p=0.004), parenting (p=0.003), food security (p=0.003), PB/U (P=0.041) and consumption patterns (iron source (p=0.008), inhibitor (p=0.026) and enhancer (p = 0.002)). After multivariate test, food security was found to be the dominant factor of anemia in baduta with OR 10,052.